Ideologi dan Politik Identitas - Bagaskara, Faishal Sultan (Indonesia Center for Middle East Studies, 2023)
The dynamics of the Palestinian struggle are also colored by the communist movement. This article discusses one of the periods of development of communism in Palestine, namely the founding of the Palestinian Communist Party (PCP) in 1923-1982. PCP was initially founded and dominated by Jewish immigrants from Russia. After officially joining the Communist International (Comintern), they received instructions to carry out Arabization within their party. This Arabization aims to enable the PCP to recruit Arabs and support the struggle of the Arab community, which is the majority in Palestine. This article analyzes the PCP's failure to unite Arabs and Jews, which was caused by differences in political interests. This research uses a narrative and empirical historical approach using critical historical methods (heuristics, verification, interpretation and historiography). The theory used in this research is the theory of ideology and identity politics. The findings of this research are that the emergence of identity politics between Arabs and Jews in the PKP has led to several internal (Arabization) and external policies (British White Paper 1939), which resulted in a dualism that thwarted their efforts to become a revolutionary party against British colonialism in Palestine.